Pengembangan Perangkat Model Blended Learning untuk Meningkatkan Efektivitas Penerapan Pendidikan Jarak Jauh di SMKN 2 Gerung - Muzakkir, Muzakkir; Wibawa, Restu; Astutik, Fitri; Muhakkikin, Muhakkikin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2018)
Abstract: This study aims to develop a set of blended learning models to improve the effectiveness of the application of a long distance education in SMK 2 Gerung. This research used research and development (R &Â D). This research developed learning tools that support the effectiveness of the blended learning application.Â The tools to be developed were modules, syllabus, learning implementation plans and guidebooks forÂ Schoology use. Product development process was done through the stages of defining, designing andÂ developing after being tested. The design of this study was only one group for the implementation of productÂ testing. The research was conducted in Class X of SMK 2 Gerung West Lombok. Based on the results ofÂ students learning data, it was obtained asymp values. Sig = 0.000 which means smaller than <0.05. So, it canÂ be concluded that there is a difference between students learning outcomes of pretest and posttest which meansÂ that the blended learning model can increase the effectiveness of long distance education. The mastery of theÂ standard score of learning outcomes for posttest scores = 84 from the value of the standard score 72 and theÂ percentage of students who complete up to 80%. Based on the responses of students, it was found as much asÂ 80% of students who answered the criteria of Strongly Agree (ST). From these results, the tools of the blendedÂ learning model can support the effectiveness of the implementation of long distance education. Â Abstrak: Penelitian ini bertujuan untuk mengembangkan perangkat model blended learning untuk meningkatkan efektivitas penerapan pendidikan jarak jauh di SMKN 2 Gerung. Penelitian ini termasuk jenisÂ reaserch and development (R&D). Melalui penelitian ini akan mengembangkan perangkat pembelajaran yangÂ mendukung efektivitas penerapan blended learning. Perangkat yang akan dikembangkan berupa modul,Â silabus, rencana pelaksanaan pembelajaran dan buku panduan pemanfaatan Schoology. Proses pengembanganÂ produk melalui tahap pendefinisian (define), perancangan (design), dan pengembangan (develop) setelah ituÂ diuji coba. Desain penelitian ini hanya satu kelompok untuk pelaksanaan uji produk. Penelitian dilaksanakan diÂ Kelas X SMKN 2 Gerung Lombok Barat. Berdasarkan olah data hasil belajar siswa diperoleh nilai Asymp.SigÂ = 0.000 artinya lebih kecil dari < 0.05. Sehingga dapat disimpulkan bahwa ada perbedaan antara hasil belajarÂ siswa untuk pretest dan postest artinya perangkat model blended learning dapat meningkatkan efektivitasÂ pendidikan jarak jauh. Ketuntasan hasil belajar rata-rata nilai postest = 84 dari nilai KMM 72 dan presentaseÂ siswa yang tuntas 80%. Berdasarkan respon siswa sebanyak 80% siswa yang menjawab pada kriteria Sangat Setuju (ST). Dari hasil tersebut bahwa perangkat model blended learning dapat menunjang efektivitas pelaksanaan pendidikan jarak jauh.